2019
DOI: 10.3389/fnins.2019.00661
|View full text |Cite
|
Sign up to set email alerts
|

Music to One’s Ears: Familiarity and Music Engagement in People With Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a complex diagnosis commonly associated with motor dysfunction, but known to comprise cognitive, psychiatric, and mood disturbances as well. Music has been successfully used to address motor and non-motor symptoms of PD. Still, little is known about the nature of an individual with PD’s experience and relationship with music on conceptual and emotional levels, which may factor into their engagement in music-based techniques to ameliorate impairments. Two surveys were administered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Taken together, these results suggest that people with PD may require encouragement to participate, as well as to the ability to choose familiar selections to better access music-based interventions and the benefits they may offer. This may facilitate adherence to therapy, as music is engaging and enjoyable [ 34 ], improves mood, depressive syndromes [ 48 ], and thus improves the quality of life for people with PD [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results suggest that people with PD may require encouragement to participate, as well as to the ability to choose familiar selections to better access music-based interventions and the benefits they may offer. This may facilitate adherence to therapy, as music is engaging and enjoyable [ 34 ], improves mood, depressive syndromes [ 48 ], and thus improves the quality of life for people with PD [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Music listening not only activates emotional networks but also stimulates dopamine production in the striatal system (Salimpoor et al, 2011). Emotions and physical movements are closely intertwined (Molnar-Szakacs and Overy, 2006), hence there are suggestions that motor improvements following music intervention may be a result of emotional reactions mediating the dopaminergic activity of the BG motor loop (Salimpoor et al, 2011;Morris et al, 2019). A recent PET study by Koshimori et al (2019) explored RAS-induced dopamine responses in the BG of healthy participants while they performed finger-tapping tasks.…”
Section: Neurochemical Effects Of Rasmentioning
confidence: 99%
“…This study, therefore, provided insights about the potential role of RAS to modulate dopamine responses in PD and warrant future studies with PD patients. Morris et al (2019) surveyed the music responses of people with and without PD. They observed that PD patients had a diminished connection between music and action, compared to controls who perceived music as a reward and felt motivated to sing or dance along.…”
Section: Neurochemical Effects Of Rasmentioning
confidence: 99%
See 1 more Smart Citation
“…Familiar music favors prediction and anticipation [ 18 ]. Moreover, preferred familiar music gives greater enjoyment and increases emotional engagement as well as compliance with the rehabilitation training programs [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%